Analisis Kinerja Keuangan Pada Mitra PT. Cipta Aneka Selera (studi kasus Yasaka Freid Chikend Pandan) - Annnisa Pasaribu; Yenni Soflana Tambunan; Kaharuddin Simamora (CV. Aksara Global Akademia, 2023)
This study aims to find out the financial performance of partners in PT. Cipta Aneka Selera (Case Study of Yasaka Fried Chicken Pandan, Central Tapanuli Regency). The population and sample of this study are the financial statements of Partners of PT.Aneka Selera (Case Study of Yasaka Freid Chicken Pandan). The research method used is a quantitative method with a descriptive approach, the test used is the Data Analysis Test. The results of the research show that the results of the analysis of financial performance on Partners of PT. Cipta Aneka Selera (a case study of Yasaka Fried Chicken Pandan) where it was found that Return On Assets (ROA) tended to decrease, this was due to decreased sales, Pandan, causing a decrease in profits which resulted in a decrease in ROA value from 2017 of 3.64% to 1, 47% in 2018 so it has not met the Ministry of BUMN assessment standards B-PER10/MBU/2014. While Return On Equity (ROE) in 2019 to 2021 has decreased. And the value of ROE in 2017 to 2018 has not met the ministry's assessment standards. The current ratio for financial performance can be said to be good.